Digital Transformation and Employment: Challenges for Human Resource Use and Management - Thu Trang, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 39 No 3, 2023)
The transition from "human" to "machine" has become the objectives and means for countries' economic progress. In the long run, this approach will provide new and better job prospects for employees. However, for social science researchers, "unemployment due to technological innovation" is a source of concern because the transition process for jobless individuals to find new occupations can be lengthy, particularly for the group of untrained, low-skilled employees. The purpose of this study is to present a summary of prominent concepts used domestic and international scholars and researchers to explain the impact of technology on workers' employment dynamics. The study uses a conceptual approach through a review of related documents to analyze the impact of technology in general and digital transformation in particular on employment in general. In the context of the fourth industrial revolution, the article also illuminates discussions regarding altering the nature of work, particularly those pertaining to employment polarization and unemployment brought on by labor technology.